The Development of Student Worksheet Based on Discovery Learning of Nervous System Material to Train Critical Thinking Skills of 11th Grade Students - Rahmadhia, Shinta Naurah; Qomariyah, Nur (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2024)
Critical thinking is one of the demands of 21st-century learning, the lack of teaching materials that train critical thinking skills and conventional learning results in low student learning outcomes. This study aims to produce a student worksheet of Discovery Learning-based on Nervous System material to train the critical thinking skills students of grade 11th with the valid, practical, and effective. This type of research was a development research with the ADDIE model, the data collection method uses validation methods for the level of validity, observation and questionnaire methods for the level of practicality, and test methods for the level of effectiveness, which were analyzed using qualitative and quantitative descriptive methods. The average validation result was 3.87, with very valid criteria. The results of practicality based on the implementation of learning were 96,87% and based on the results of questionnaires of 97%, both them got very practical criteria. The effectiveness results based on the completeness of learning outcomes of 100% with an average score of 91.5 are included in the effective criteria, then based on critical thinking skills by 90% on the indicators of critical thinking interpretation, and 93.75% on the indicators of critical thinking analysis and inference, with a very high category. It can be concluded that the developed student worksheet is valid, practical, and effective. Keywords: student worksheet, Discovery Learning, critical thinking, nervous system.